Multimodal characterization of solution-processed Cu3SbS4 absorbers for thin film solar cells. Issue 18 (25th April 2018) - Albuquerque, Gustavo H.; Kim, Ki-Joong; Lopez, Jonathon I.; Devaraj, Arun; Manandhar, Sandeep; Liu, Yi-Sheng; Guo, Jinghua; Chang, Chih-Hung; Herman, Gregory S.
Abstract : Optimized sulfurization process and final spectrum of the absorption coefficient of the Cu3 SbS4 thin films. Abstract : The most efficient inorganic thin film chalcogenide-based solar cells use CdTe or CuInGaSe2 (CIGS) as absorber layers, which rely on toxic (Cd) and/or scarce elements (In, Te). The desire for more sustainable solar cells has led to the development of Earth abundant and non-hazardous chalcogenide absorbers. Cu3 SbS4 (famatinite) is a promising Earth abundant p-type semiconductor that has a low direct band gap (0.9–1.05 eV), is a superabsorber (absorption coefficient ∼ 10 4 –10 5 cm −1 ), and has potential in low-cost, thin-film solar cells. Although these properties make the Cu3 SbS4 phase stand out as a promising material for photovoltaics, to date Cu3 SbS4 solar cells have only achieved low efficiencies. In this study, we demonstrate a method for synthesizing Cu3 SbS4 nanocrystals and formation of thin-films by coating nanocrystal precursors onto substrates. Optical, structural, and chemical state characterization were performed before and after thermal processing of the Cu3 SbS4 films. A detailed experimental analysis of the bulk and surfaces of the Cu3 SbS4 absorber films indicate that phase stability and preferential copper oxidation at the surface may limit device performance for Cu3 SbS4 based solar cells. These findings may provide significant insight on how to improve Cu3 SbS4 based solar cell performance by controlling processing conditions.